The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/chem.201604903
|View full text |Cite
|
Sign up to set email alerts
|

A Bio‐Chemosynthetic Approach to Superparamagnetic Iron Oxide–Ansamitocin Conjugates for Use in Magnetic Drug Targeting

Abstract: A combination of mutasynthesis using a mutant strain of A. pretiosum blocked in the biosynthesis of amino-hydroxybenzoic acid (AHBA) and semisynthesis relying on a Stille cross-coupling step provided access to new ansamitocin derivatives of which one was attached by a thermolabile linker to nanostructured iron oxide particles. When exposed to an oscillating electromagnetic field the resulting iron oxide/ansamitocin conjugate 19 heats up in an aqueous suspension and the ansamitocin derivative 16 is released by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…This reaction has advantageous characteristics for cargo release: it is self‐contained, that is, all atoms present in the diene and dienophile remain in the resulting products, and displacement of the equilibrium is governed by temperature, solvent, or reactant concentration, and not by external molecules, such as water, metal catalyst, or bases/acids . IONs are known to produce heat if placed under an AMF in a phenomenon known as magnetic hyperthermia, which can be used to induce the release of cargo molecules attached to the NPs through thermosensitive bonds . The hyperthermia temperature profile is dependent on the distance from the ION surface; the highest temperature is reached at the surface and decreases exponentially with increasing distance .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction has advantageous characteristics for cargo release: it is self‐contained, that is, all atoms present in the diene and dienophile remain in the resulting products, and displacement of the equilibrium is governed by temperature, solvent, or reactant concentration, and not by external molecules, such as water, metal catalyst, or bases/acids . IONs are known to produce heat if placed under an AMF in a phenomenon known as magnetic hyperthermia, which can be used to induce the release of cargo molecules attached to the NPs through thermosensitive bonds . The hyperthermia temperature profile is dependent on the distance from the ION surface; the highest temperature is reached at the surface and decreases exponentially with increasing distance .…”
Section: Resultsmentioning
confidence: 99%
“…[22] IONs are known to produce heat if placed under an AMF in ap henomenonk nown as magnetic hyperthermia, [33] which can be used to induce the release of cargo molecules attached to theN Ps through thermosensitive bonds. [23,24,[34][35][36] The hyperthermia temperature profile is dependento nt he distance from the ION surface; the highest temperature is reached at the surface and decreases exponentially with increasing distance. [37] Maleimide-Alkyne-Fe 3 O 4 is designed to place the cargo molecules only af ew ångstrçms away from the surface of the inorganic core and allow magnetic hyperthemia to sufficiently increaset he local temperature to trigger release.…”
Section: Diels-alder and Cuaacc Ycloadditionsmentioning
confidence: 99%
“…We therefore had to utilise two different generator/inductor devices in the present study (for more information see Table and the Supporting Information). Both devices are equipped with high‐frequency inductors (650–1000 kHz), since medium‐frequency inductors were inefficient to generate enough heat inside small samples of the MAGSILICA® nanostructure particles 8 d in order to efficiently release the toxin 5 d into the aqueous medium ,…”
Section: Resultsmentioning
confidence: 99%
“…It enables a retro ‐Diels–Alder reaction at higher temperatures to cleave off bound organic molecules. In our recent report we demonstrated that such a thermosensitive linker can be attached to the aromatic ring at the 19‐position without leading to substantial reduction of bioactivity . In the present work, maleimide‐modified MAGSILICA® ( 7 ) is merged with suitable ansamitocin derivatives bearing a furan group in the ester side chain at C‐3.…”
Section: Introductionmentioning
confidence: 82%
“…The furan and maleimide Diels–Alder pair has also featured heavily in our own work, developed over a number of years in combination with new technology in the area of mutational biosynthesis (“mutasynthesis”) . Silica‐coated SPIONs were first functionalized with maleimide, then loaded with antiproliferative furan‐ligated ansamitocin derivatives by heating to 62 °C in acetonitrile for three days ( Scheme ).…”
Section: Thermal Cleavage Of Temperature‐sensitive Covalent Linkersmentioning
confidence: 99%